Corporate Taxation of Foreign Direct Investment Income 1991-2001 - Yoo, Kwang-Yeol (OECD Economics Department Working Papers, 2003)
This paper constructs indicators of tax burden on FDI in order to review their trends and cross-country patterns. Over the 1990s, the overall tax burden on inward FDI (measured by the effective marginal tax rates) fell by 8 percentage points, reflecting corporate tax reforms in some OECD countries. Nevertheless, a large variation across host countries still remains. With the effective tax rates on inward FDI differing across host countries by as much as 28 percentage points for marginal FDI and by as much as 21 percentage points for infra-marginal FDI in 2001, a cross-country comparison of tax burden indicators shows that, irrespective of the tax burden indicators chosen, Canada, Iceland and Japan are persistently ranked as high-tax host countries over the 1990s. It is also found that there is more variation in the tax burdens faced by a parent company operating in different host countries than in the tax burdens faced by subsidiaries from different home countries operating in the ...